HUBUNGAN TINGKAT PENGETAHUAN TENTANG KEBERSIHAN GENETALIA DENGAN KEJADIAN KEPUTIHAN PADA SISWI SMA KELAS XI IPA DI SMA NEGERI 1 TAWANGSARI - Indriati, Ratna; Dwi Ningsih, Endang; Novita Sari, Eni (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2014)
AbstractThe background One problem adolescent reproductive health, especially of ladies often complained is whitish.One factor affecting the whiteness is the lack of knowledge about clean genetalia who holds an important role in preventing infection can cause a whitish.At the beginning the research gained 10 students performed interview seven students know about cleaning genetalia and three other students lack knowledge about clean genetalia.Of 10 students are known 4 students ever had that experience whitish and most of them are students who lack knowledge about clean genetalia. The aim of this research is to find the knowledge about clean genetalia relations with whitish in the students of class XI IPA at SMA 1 Tawangsari. The design of the correlation with a method of cross sectional. Responden is 92 students of class XIIPA in SMA 1 tawangsari with a random sample taking a simple sampling.Data obtained by this method a questionnaire to know the level of knowledge about clean genetalia and the whiteness of the respondents.Which have collected data and analysis by the chi square with p =0.05 The results show the high level of as many as 81 people ( 88,04 % ) and medium category 11 people ( 11,96 % ), whiteness category is 38 people ( 41,3 % ), and not to whiteness 54 people ( 58,7 % ).Analysis of the results obtained using chi square p = 0.004 so p < 0.05, and value which means Ho rejected and Ha accepted. The Conclusion of the research was there is relationship of the knowledge about clean genetalia with whitish in the students of class XI IPA at SMA 1 Tawangsari.Keywords: Level of Knowledge, Health genetalia, whitish